The Effectiveness of Audio-Visual Learning Media in Visual Arts Subjects: A Literature Review - Irawan, Andi; Wardoyo, Sugeng (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The appropriate use of learning media can significantly influence students' motivation and learning outcomes. However, in the process of teaching visual arts, several issues often arise, such as: (1) students easily become bored because the learning media used are still conventional, such as black-and-white textbooks; (2) the delivery of material by teachers is less effective, resulting in students not fully understanding the material taught; (3) limited time for delivering both theoretical and practical aspects of art-making; and (4) a lack of innovation in the use of learning media by teachers. Therefore, selecting appropriate learning media is crucial to support the success of the teaching and learning process. This study aims to complement previous research that has been limited in reviewing literature related to the effectiveness of audio-visual learning media, particularly in visual arts subjects focusing on decorative motifs and the application of media in creative work. This research uses a literature review method by searching for scientific articles published between 2016 and 2024 via Google Scholar. The analysis in this study applies the PRISMA framework, which includes title, abstract, introduction, method, results, discussion, and conclusion. The findings of this study show that audio-visual media successfully increase students’ motivation and learning outcomes, attract their interest in learning, and provide new experiences in the learning process, especially considering that they were previously more accustomed to conventional media such as textbooks. The author discovered alternative media for creating decorative motif artworks using the batik technique, including dried banana leaves, lantung bark, teak wood, sengon wood, munggur wood, and klepu wood. This paper is expected to contribute new knowledge for teachers by offering references for creating decorative motif artworks through other creative media.